Navigating the Aftermath: U.S. Policy in Afghanistan Following Troop Withdrawal - Z. Makoveeva (Vestnik MGIMO-Universiteta)
The withdrawal of US troops from Afghanistan in the middle of 2021 has put at stake and turned to shock the world community. The world, which was fighting COVID-19, faced more concerns about the US withdrawal from Afghanistan. It became not only a concern of Middle East countries, but it raised questions in Europe too. While the Middle East countries were anxious about security issues in the region, Europe was anxious about the mass migration of refugees. Russia, the country which is crucially interested in stable peace in the Middle East, and China, which is cooperating with Afghanistan in the economic sector, began negotiations with the Taliban government to stabilize the situation peacefully after the withdrawal of American troops.The article analyzes the changes in US policy in Afghanistan after the withdrawal of troops in August 2021. The withdrawal of the US military contingent from Afghanistan has changed the balance of power in Central Asia, which, on the one hand, creates new risks to international security, and on the other hand, opens up new opportunities for interested players in the international arena in the region. In the new conditions, the United States is forced to restructure its policy towards Afghanistan and change its security strategy in accordance with the new balance of forces in the region. The findings of the study relate to the actual interests of the United States in the field of security in Afghanistan and in the Central Asian region as a whole.